Phytoestrogens and Sirtuin Activation for Renal Protection: A Review of Potential Therapeutic Strategies - Mandal, Debojyoti; Akhtar, Nahid; Shafi, Sana; Gupta, Jeena (Planta Medica, 2025)
Significant health and socio-economic challenges are posed by renal diseases, leading to millions of deaths annually. The costs associated with treating and caring for patients with renal diseases are considerable. Current therapies rely on synthetic drugs that often come with side effects. However, phytoestrogens, natural compounds, are emerging as promising renal protective agents. They offer a relatively safe, effective, and cost-efficient alternative to existing therapies. Phytoestrogens, being structurally similar to 17‐β‐estradiol, bind to estrogen receptors and produce both beneficial and, in some cases, harmful health effects. The activation of sirtuins has shown promise in mitigating fibrosis and inflammation in renal tissues. Specifically, SIRT1, which is a crucial regulator of metabolic activities, plays a role in protecting against nephrotoxicity, reducing albuminuria, safeguarding podocytes, and lowering reactive oxygen species in diabetic glomerular injury. Numerous studies have highlighted the ability of phytoestrogens to activate sirtuins, strengthen antioxidant defense, and promote mitochondrial biogenesis, playing a vital role in renal protection during kidney injury. These findings support further investigation into the potential role of phytoestrogens in renal protection. This manuscript reviews the potential of phytoestrogens such as resveratrol, genistein, coumestrol, daidzein, and formononetin in regulating sirtuin activity, particularly SIRT1, and thereby providing renal protection. Understanding these mechanisms is crucial for designing effective treatment strategies using naturally occurring phytochemicals against renal diseases.
Keywords: phytoestrogen; SIRT1; kidney disease; genistein; formononetin; resveratrol